Interventional Procedures of the Spine - Santiago, Fernando Ruiz; Kelekis, Alexis; Álvarez, Luis Guzmàn; Filippiadis, Dimitrios K. (Seminars in Musculoskeletal Radiology, 2014)
Different interventional procedures performed under imaging guidance permit the diagnosis and treatment of the many causes of back pain. Sources of pain amenable to be treated include facet joints, vertebral body, intervertebral disk, and paraspinal structures including nerves and ganglion roots. These procedures may be merely diagnostic, therapeutic, or intended for both purposes. We review the main indications, advantages, and complications of these techniques.
Keywords: spine; interventional radiology; imaging guidance